Extracellular metabolites profile of different stages colorectal cancer cell lines / Hazwani Mohd Yusof … [et al.] - Mohd Yusof, Hazwani; Ab-Rahim, Sharaniza; Wan Ngah, Wan Zurinah; Nathan, Sheila; A Jamal, A Rahman; Mazlan, Musalmah (Faculty of Applied Sciences and UiTM Press, 2021)
Metabolic footprinting involves the determination of metabolites excreted or secreted by the cells. This study aimed to identify the differential extracellular metabolites in colorectal cancer (CRC) cells for the determination of molecular changes that occur as CRC progresses. CRC cells at different stages ie; SW 1116 (stage A), HT 29 and SW 480 (stage B), HCT 15 and DLD-1 (stage C), and HCT 116 (stage D) were grown in culture. The media in which the cells were grown are subjected to metabolomics profiling using Liquid Chromatography Mass SpectrometryQuadrupole Time of Flight (LC/MS Q-TOF). Statistical and metabolic pathway analysis was performed using Metaboanalyst software and identification of metabolites was determined by the METLIN database. A total of 27 differential extracellular metabolites were identified in CRC cells of different stages compared to stage A cells. Data from the Partial least squares-discriminant analysis (PLS-DA) score plot shows a clear separation between CRC cells of different stages with a few overlaps between stage B and C. Further analysis using variable importance in projection (VIP) revealed 14 differential extracellular metabolites that were most significant in differentiating CRC cells of the advanced stages from stage A which are 5-hydroxy-L-tryptophan, indoleacetaldehyde, 4,5-dimethylthiazole, 8-oxodiacetoxyscirpenol, bisnorbiotin, 5-amino-6- (5'phosphoribosylamino) uracil, glyceryl 5-hydroxydecanoate, sphinganine, 8,8-diethoxy-2,6- dimethyl-2-octanol, l-cystine, thiamine acetic acid, phytosphingosine, PE (20:4(5Z,8Z,11Z,14Z)/22:6(4Z,7Z,10Z,13Z,16Z,19Z)), N-(2R-hydroxypentacosano-yl)-2Samino-1,3S,4R-octadecanetriol. The different expressions of metabolites may indicate altered metabolic pathways in the more advanced CRC cells compared to stage A. This study highlights the importance of conducting both metabolomics profiling of extracellular and intracellular to generate a more complete understanding on the molecular changes that occur as CRC progresses.